A Diagnostic Test of Tinea Cruris Using Polymerase Chain Reaction Restriction Fragmented Length Polymorphism - Hazlianda, Cut Putri; Muis, Kamaliah; Lubis, Isma Aprita (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Tinea cruris is the second most common dermatophytosis in the world and the most common in Indonesia. The conventional diagnostic method fungal culture is slow and less specific, therefore requiring a more rapid and exact diagnostic methods. Polymerase chain reaction (PCR) is a very sensitive and specific test to diagnose various microorganisms including pathogenic fungi. Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) is a PCR method with the addition of enzyme after amplification, therefore enabling for more specific results. Purpose: To determine the diagnostic value of PCR-RFLP in the diagnosis of tinea cruris. Methods: This study is a diagnostic test tinea cruris with PCR-RFLP by using culture as the gold standard. The specimens were skin scrapings from thirty-one patients suspected of having tinea cruris from history taking and dermatological examination. The tools and materials that were used in this study were Sabaroud’s dextrose agar media, Internal Transcribe Sequences (ITS) 1 and ITS 4 primer, and MvaI. Results: The values of the diagnostic test yielded in this study are: the sensitivity value was 75%, the specificity was 66.7%, the positive predictive value was 70.6%, the negative predictive value was 71.4%, the positive likelihood ratio was 2.25, the negative likelihood ratio was 0.38, the accuracy value was 70.9%. Conclusion: PCR-RFLP can be used as an alternative tool for the diagnosis of tinea cruris.